(untitled) (Computer systems and information technologies, 2021)
The paper further develops the mathematical model of the software design technology (SDT) and the criteria for evaluating the SDT, which allow experts to evaluate each considered software design technology more accurately, taking into account all its components. The method and production rules of the selection of the software design technology proposed by the authors give the organization the opportunity to make a motivated and reasonable choice of the design technology for its further implementation